2013
DOI: 10.1007/s00431-013-2198-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency among native Dutch and first- and second-generation non-Western immigrants

Abstract: Vitamin D deficiency in the paediatric population is still a matter of concern in the Netherlands, in particular among first-generation non-Western immigrants. We therefore strongly recommend vitamin D supplementation for all non-Western immigrants, regardless of age, skin type or season. Health-care staff who work with non-Western immigrants should be aware of the prevalence and implications of vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…3 . In a recent cohort study of mother-infant pairs, it was shown that 3-epi-25(OH)D 3 is present at low levels in some pregnant women and fetuses but does not appear to be efficiently transferred transplacentally (20).…”
Section: Origin Of 3-epi-25(oh)dmentioning
confidence: 99%
See 3 more Smart Citations
“…3 . In a recent cohort study of mother-infant pairs, it was shown that 3-epi-25(OH)D 3 is present at low levels in some pregnant women and fetuses but does not appear to be efficiently transferred transplacentally (20).…”
Section: Origin Of 3-epi-25(oh)dmentioning
confidence: 99%
“…Also, the physiological importance of the C 3 -epimer is heavily debated. In vitro work and rodent models show that 3-epi-25(OH) D 3 and the epimeric form of calcitriol (3-epi-1α,25(OH) 2 D 3 ) bind vitamin D binding protein at 36-46% and vitamin D receptor at 2-3% as compared with non-epimer 25(OH)D 3 and calcitriol (15). However, 3-epi-1α,25(OH) 2 D 3 appears nearly as potent as calcitriol in suppressing parathyroid hormone (16), but it has significantly reduced calcemic effects (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Results of studies in many countries and also national data on Dutch children indicate that prevalence of vitamin D deficiency is not expected to differ in children with or without a fracture (14,17,18,20,21,33,34). Thus, routine vitamin D measurement in children with a fracture should be avoided.…”
Section: Discussionmentioning
confidence: 99%